PENGUKURAN SEDIMEN TERLARUT DI MUARA DESA NUSAPATI KECAMATAN SUNGAI PINYUH KABUPATEN MEMPAWAH - Hasmiza, Maya; Herawatiningsih, Ratna (JURNAL HUTAN LESTARI, 2017)
Nusapati village is one of the villages located in Subdistrict of Sungai Pinyuh Mempawah Regency. Currently, the depth of the river in Nusapati village is only 5.3 meters. This situation resulted in flooding and a negative impact on economic activities of the fishing communities around Nusapati River. This change is caused by the sedimentary material carried by the flow of the river from inland or carried by the currents of the sea. Another factor affecting the sedimentation in the estuary of the river, among others: the activities of the wave and current patterns. The problem is not known as to how much of the sediment in the river estuary of Nusapati village. This aims to measure the dissolved sediment in the estuary of Nusapati village of Sungai Pinyuh Subdistrict in Mempawah Regency. The sampling method in this study used a purposive sampling method. This research was carried out using direct measurement at the estuary of the river to get the data on the flow rate and sediment concentration. Samples of sediment concentrations were analyzed in the laboratory. The results showed that the value of dissolved sediment concentration ​​obtained was quite high at the location, namely when the tide is low that is 53.567 mg/L at point 3A. The dissolved sediment was considered good. The highest concentration of dissolved sediment value was equal to 53.567 mg/L at the location of point 3 was at point 3C and the lowest value of 0,550 mg/L on the location of point 1 namely at the point A1 during low tide conditions. The flow rate ​​at point 3 namely 3C was at 0.083 m/second, while at the location of point 1 namely 1A at 0.092 m/second. During low tide, the highest flow rate value was 0.092 m/second at location 1 the highest flow rate value was 0.076 at location 2. Keywords: Dissolved Sediment, Estuary, Nusapati village.